NU, TOKOH DAN PENDIDIKAN - Fathul khair; Bahaking Rama; Muh Rusydi Rasyid (ADIBA : JOURNAL OF EDUCATION, 2023)
NU was partly founded by students who were always persistent against colonialism, responding to the national awakening by forming movement organizations, such as Nahdlatul Wathan (Revival of the Motherland) in 1916. Then in 1918 Taswirul Afkar or also known as "Nahdlatul Fikri" (revival of thought) was founded, as a vehicle for socio-political and religious education of the students. Nahdlatut Tujjar was founded, (merchant movement). The union was used as a base to improve the people's economy. Nahdlatul Tujjar is, hence Taswirul Afkar. Departing committees and various organizations that are embryonal, then after that it is necessary to form a more inclusive and more systematic organization, in order to anticipate the development of the times. So after coordinating with various kyai, an agreement finally emerged to form an organization called Nahdlatul Ulama on 16 Rajab 1344 H (January 31, 1926). The organization was led by K.H. Hasyim Asy'ari as Rais Akbar.